Wang Qiang. ([S.l.] : [s.n.], 2001)
As an artist, so many years I have never got my varied and orderless works sorted out for a catalogue of my own works. Thanks to the great support of many friends, I eventually have it edited and published. My works have no certeinty in style and will not have in future while they are relatively coherent in thoughts. That is how I want it to be. This catalogue shows the "harvest" of my work during the last few year. Her borth means warm oven and cool in the first hard winter in the 21 century to me. Wang, Qiang 2001-11-16
biog., ind. tent., gr. tent. prijzen p. 79
Chinees
Engels
boek
Keywords: Wang, Qiang